Analysis of The Completeness of The Medical Resume of Maternity Patients at Nashrul Ummah Lamongan Islamic Hospital - Devi Salsa Yuniartha; Suharyono; Lilis Maghfuroh; Atiul Impartina; M. Ganda Saputra; Arif Banar Rizali; Dadang Kusbiantoro (Jurnal Surya, 2024)
Introduction: A medical resume is a summary of the medical services provided by a health professional, especially a doctor, during treatment until the patient is discharged, either alive or dead. The purpose of this study is to determine the percentage and factors that cause the completeness of the medical resume of maternity patients at RSI Nashrul Ummah Lamongan. Methods: The design in this study is a combination of sequential explanatory research that combines quantitative and qualitative research methods sequentially. The number of samples is 72 medical resumes for the End of the Year 2022. Results: Almost all (97%) complete patient identification fills out and a small part (4%) of 3 incomplete medical resumes. The completeness of filling out important reporting is all (100%) fully filled and a small part (8%) of 6 medical resumes are incomplete. The completeness of filling out the authentication is almost entirely (99%) complete and a small part (3%) of 2 medical resumes are not filled out completely. The completeness of documentation based on the recording is clearly read on the medical resume sheet which is complete (100%) complete as many as 73 medical resume sheets and a small part (1%) is incomplete. Conclusion: The factor causing the delay in filling out a medical resume is time constraints caused by busyness and other work demands from the doctor in charge. The socialization of filling out the medical resume as well as Monitoring and Evaluation should be carried out to the maximum. Keywords: Health worker, Knowledge, Occupational Health and Safety (K3)